A glance at the Ethiopian higher education from the developmental state perspective - Ayenachew Assefa Woldegiyorgi (Bahir Dar Journal of Education)
Modern higher education in Ethiopia has a short history of a little over six decades. Over the past two decades there have been tremendous reforms that aimed at expanding and modernizing the higher education subsector so that it would make meaningful contributions for the country’s development. However, despite the rapid expansion of the sector, its process and roles have not become a research agenda to assess whether Ethiopia is following the ‘right path’ of the developmental state model in its various economic and social policies. Therefore, this study attempts to shed light on the nature of the Ethiopian higher education taking the perspective of the developmental state paradigm. Based on the method of document analysis, the findings of the study indicate that the Ethiopian higher education shows strong manifestations of the characteristics which were evident in those developmental states in early stage. Strong state control, central admission process, focus on certain priority areas, massive expansion, emphasis on technology transfer and using higher education to serve non-economic national agendas are typically observable in the Ethiopian higher education system. The study has also identified some inconsistencies and shortcomings. For instance, the Ethiopian higher education falls short in terms of institutional diversity, adequacy of research on technology transfer, and the role of the private sector. Finally, some implications are highlighted to pinpoint the areas worthy of more detailed policy research